2022
DOI: 10.3390/ma15207185
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Switching Characteristics of Transparent WOX-Based RRAM for Synaptic Application and Neuromorphic Engineering

Abstract: In this work, we evaluate the resistive switching (RS) and synaptic characteristics of a fully transparent resistive random-access memory (T-RRAM) device based on indium-tin-oxide (ITO) electrodes. Here, we fabricated ITO/WOX/ITO capacitor structure and incorporated DC-sputtered WOX as the switching layer between the two ITO electrodes. The device shows approximately 77% (including the glass substrate) of optical transmittance in visible light and exhibits reliable bipolar switching behavior. The current-volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Likewise, the green and pink doublets correspond to the W 5+ oxidation state and the W 4+ oxidation state, respectively. The spectrum of O 1s has doublet peaks, of which one is oxygen deficiency (532.08 eV) and the other is W-O bonding (531.21 eV) [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the green and pink doublets correspond to the W 5+ oxidation state and the W 4+ oxidation state, respectively. The spectrum of O 1s has doublet peaks, of which one is oxygen deficiency (532.08 eV) and the other is W-O bonding (531.21 eV) [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the cost and commercial availability should be considered when choosing materials for the RRAM. In addition, if indium tin oxide (ITO) is selected as an electrode, the device can be employed in light-based applications, such as transparent memory [ 35 ], photodetectors [ 36 ], and displays, owing to its transparency [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its low (≥10) I ON /I OFF ) ratio, this device has a lower switching voltage than other organic ReRAM devices, but its endurance of only 30 cycles is a drawback for non-volatile memory applications. Future electronic gadgets, on the other hand, appear to be flexible [15], transparent [15,16], and transient [17]. Yalagala et al reported on the rapid (<4 s) dissolving of a ReRAM device with a MgO-PVP-Ge active layer and Ag and ITO electrodes [17].…”
Section: Transport and Memory Studymentioning
confidence: 99%
“…To date, RRAM devices with a variety of oxides have been researched for synaptic device application, such as HfO 2 , 13–15 Ta 2 O 3 , 16–18 WO x , 19–21 TiO 2 , 22–24 CeO 2 , 7,25,26 ZnO, 27–29 NiO, 30–32 SrFeO x , 33 and PCMO. 34,35 With respect to the resistance change mechanism, filamentary-type CBRAM and VCM suffer from a non-linear, digital-type and asymmetric resistance change with a large device-to-device variation due to the abrupt and stochastic nature of filament formation.…”
Section: Introductionmentioning
confidence: 99%